[Carotid artery stenting for acute stroke]. - Papanagiotou, P; Roth, C; Grunwald, I; Ahlhelm, F; Ernst, N; Haass, A; Reith, W (2009)
For patients with acute ischemic stroke due to total occlusion of the internal carotid artery (ICA), an effective intervention to improve neurologic symptoms and clinical outcome has not yet been established. Some authors have reported successful revascularization for patients with acute stroke symptoms secondary to ICA occlusion only in isolated series and case reports. Emergency recanalization and carotid artery stent placement can improve neurologic outcome in selected patients with acute ischemic stroke and total occlusion of the ICA.